Gender roles and dynamics in COVID-19 times: Changes and continuities in sharing arrangements of housework and caregiving - Santos, M. H.; Rosa, M.; Correia, R.; Xavier, E. (Psicologia, 2021)
This paper intends to understand the effects of the COVID-19 pandemic on shared unpaid work between men and women living as a couple during the confinement, to assess whether this situation influenced family dynamics, especially when professional status changed to teleworking. With this goal, weekly hours spent in housework and caregiving, perceptions of justice about sharing arrangements, and the impact of COVID in the housework and caregiving workload were analyzed, in a sample of 128 workingage participants, living as a couple, and mostly in telework (58%). The asymmetries identified in recent literature were also found in our study, particularly for couples with underage children. Women reported doing much more work than it would be fair, both in household and caregiving tasks. Parents reported a workload increase in caregiving tasks, compared to participants without children, independently of sex.